Rapid synthesis of highly monodispersed silver nanoparticles from the leaves of Salvadora persica - Khan, Mamatha R. Shadab; Salunkhe, Pooja; Satpute, Shruti; Kendurkar, Shuchishweta; Prabhune, Asmita; Deval, Animesh; Chaudhari, Bhushan P. (Materials Letters, 2017)
We have demonstrated a one pot green protocol for the synthesis of highly monodispersed silver nanoparticles using leaves of Salvadora persica plant. When the leaf extract of Salvadora persica plant reacted with silver nitrate (AgNO3) solution it resulted in the synthesis of highly monodispersed silver nanoparticles with an average size of 3 nm. These nanoparticles were then completely characterized by UV-Visible spectroscopy, Transmission Electron Microscopy, Energy Dispersive Analysis of X-Rays, X-ray diffraction analysis and Fourier Transform Infrared analysis. (C) 2017 Elsevier B.V. All rights reserved.